Adapting individual placement and support for unemployed adults with autism spectrum disorder. - Florence, Ana Carolina; Elwyn, Glyn; Mueser, Kim T.; McGurk, Susan R.; Liebmann, Edward P.; McLaren, Jennifer L.; Drake, Robert E. (Journal of Vocational Rehabilitation, 2025)
Background: Employment benefits adults with autism spectrum disorder (ASD) in many ways, yet unemployment remains high. Existing interventions use predominantly "train-place" methods, emphasizing pre-employment training before competitive employment. As an alternative, Individual Placement and Support is a "place-train" model, originally developed for people with serious mental illness, that is rapidly spreading to new populations, including adults with ASD. Adaptations to evidence-based interventions for new groups should receive scientific validation. Objective: This article outlines the scientific steps to adapt Individual Placement and Support to serve the needs of adults with ASD. Methods: The authors describe a scientific approach to developing, implementing, studying, and disseminating Individual Placement and Support to adults with ASD. Results: A five-step approach to adapting Individual Placement and Support to adults with ASD includes 1) Involving stakeholders; 2) Examining available data from different perspectives; 3) Conducting a pilot study to establish acceptance, feasibility, proximal and distal outcomes, and adaptations; 4) Conducting comparative effectiveness research; 5) Translating research to policy. Conclusions: Evidence-based interventions can transfer usefully to new populations and settings, but the process should follow scientific methods. As an example, this article describes a scientific process for adapting Individual Placement and Support to adults with ASD.